2011
DOI: 10.1542/pir.32-3-100
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Thrive: Current Clinical Concepts

Abstract: Dr Jaffe has disclosed no financial relationships relevant to this article. This commentary does not contain a discussion of an unapproved/ investigative use of a commercial product/device.Objectives After completing this article, readers should be able to:1. Characterize the limitations of the classic dichotomy of "nonorganic" versus "organic" failure to thrive (FTT). Recognize that FTT is not a diagnosis but rather a physical sign of inadequate nutritionto support growth. 3. Know potential sequelae of FTT. 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
1
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 15 publications
1
62
1
9
Order By: Relevance
“…However, many syndromes are known to cause severely stunted growth despite a normal hormonal axis, the most notable of which are skeletal dysplasias, although these represent a selective defect in bony growth. On the other hand, generalized growth deficiency states that are nonhormonal in etiology and are not related to a negative caloric balance offer a unique opportunity to explore factors that control organismal growth at a more fundamental level and are likely to contribute to the ;90% of failure-to-thrive children in whom no specific etiology is identified (Jaffe 2011). Severe failure to thrive is commonly associated with a wide array of chromosomal aberrations, which attests to a role played by the genes in growth control, but assigning such a role to individual genes is not usually possible due to the nature of these chromosomal aberrations.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…However, many syndromes are known to cause severely stunted growth despite a normal hormonal axis, the most notable of which are skeletal dysplasias, although these represent a selective defect in bony growth. On the other hand, generalized growth deficiency states that are nonhormonal in etiology and are not related to a negative caloric balance offer a unique opportunity to explore factors that control organismal growth at a more fundamental level and are likely to contribute to the ;90% of failure-to-thrive children in whom no specific etiology is identified (Jaffe 2011). Severe failure to thrive is commonly associated with a wide array of chromosomal aberrations, which attests to a role played by the genes in growth control, but assigning such a role to individual genes is not usually possible due to the nature of these chromosomal aberrations.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…There is an organic explanation for a small minority. Non-organic failure to thrive brings with it an increased risk of physical illness, continued growth retardation as well as cognitive and emotional disturbances (Jaffe, 2011;Jolley, 2003).…”
Section: Failure To Thrive Syndromementioning
confidence: 99%
“…Nonorganic Failure to Thrive (NOFTT) is the most common cause of FTT and refers to situations where the infant is unable to receive enough food because of economic reasons, parental neglect or psychosocial problems (Jaffe, 2011;Krugman & Dubowitz, 2003;Şahin, 2002).…”
Section: Failure To Thrive Syndromementioning
confidence: 99%
“…F ailure to thrive (FTT) occurs when a child's rate of weight gain is below expectations based on age-and sex-specific growth charts (1). Although data regarding the prevalence of FTT in the United States are lacking, a 2006 Danish cohort study demonstrated a prevalence of 1.2% to 22.2% depending on the diagnostic criteria used (2).…”
mentioning
confidence: 99%
“…It has been suggested that the terms organic and nonorganic FTT be abandoned (1). Although many children may have both organic and nonorganic factors that contribute to their FTT, determining the primary etiology guides treatment for FTT.…”
mentioning
confidence: 99%